The Public Service Function of Neighborhood Heads from the Perspective of Islamic Leadership in Medan City - Ulfa, Mutiah; Katimin, Katimin; Syukri, Syukri (Journal of Public Representative and Society Provision, 2025)
This study examines the role of public service functions performed by Neighborhood Heads in Medan City from the perspective of Islamic leadership. The research aims to provide an understanding of how public service practices by Neighborhood Heads align with the principles and values of Islamic leadership, specifically in Medan City. This qualitative descriptive study employs participatory observation and in-depth interviews as the primary methods, utilizing an interview guide as a supporting tool. The in-depth interviews were conducted with informants to gain a comprehensive understanding of: 1) the public service functions of the Neighborhood Head, 2) the efforts made by the Neighborhood Head in fulfilling their responsibilities, 3) the supporting and inhibiting factors in executing their functions, and 4) the alignment of the Neighborhood Head's roles with Islamic leadership principles. The study concludes that the implementation of Islamic leadership values in public service by Neighborhood Chiefs is not limited to those adhering to the Islamic faith but is also evident among non-Muslim Neighborhood Chiefs. Some non-Muslim neighborhood heads demonstrate public service practices consistent with Islamic leadership values. The principles of Islamic leadership, such as amanah (trustworthiness), adil (justice), shura (consultation), and amar ma'ruf nahi munkar (enjoining good and forbidding wrong), have been observed in their practices. However, the principle of justice poses a challenge as Neighborhood Chiefs must operate within the regulations and policies established by the government, which may limit their ability to fully implement this principle.